Renewable energy, GDP and CO2 emissions in high-globalized countries - Mirziyoyeva, Ziroat; Salahodjaev, Raufhon (Frontiers in Energy Research, 2023)
This study investigates the links between renewable energy consumption, GDP, and CO2 emissions in high-globalized countries over the period from 1990 to 2015. We utilized fixed effects and two-step system GMM estimators. The key findings are: (1) the Environmental Kuznets Curve (EKC) is confirmed for highly-globalized countries; (2) renewable energy contributes to the decrease in CO2 emissions; (3) representation of women in parliament mitigate environmental degradation; (4) renewable energy moderates the effect of industrialization on CO2 emissions. Our findings offer several policy implications for developing countries to mitigate climate change effects.